Candida albicans in oral cavity - Kuna, Anna; Wrońska, Anna (Journal of Education, Health and Sport, 2023)
Candida albicans is a fungus that often colonizes the human body as a commensal without causing any symptoms. Several C. albicans virulence factors have been described in the literature, of which the best known are adhesion to host mucosa cells and secretion of hydrolytic enzymes. The transition from colonization to infection depends not only on the virulence of the fungus, but also on the response of the host to the invasion. This literature review focuses on the different forms of oral candidiasis, and discusses the symptoms, clinical picture and treatment of this disease.